PENGARUH BIMBINGAN ORANG TUA, KEBIASAAN BELAJAR, DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Habib Purnama; I Komang Winatha; Nurdin Nurdin (FKIP Unila, 2013)
This study aims to determine whether there is influence of parental guidance, study habits, and learning environments on learning outcomes IPS Integrated semester of eighth grade students of SMP PGRI 2 Labuhan Ratu of the school year 2012/2013. The population in this study were all students of class VIII, amounting to 90 students and all of them were sampled because the population is less than 100 subjects. The method used in this research is descriptive method of verification with ex post facto approach and survey. Data were collected through questionnaires, processed by computer through SPSS version 16. To test the hypothesis first, second, and third using simple linear regression, while the fourth hypothesis using multiple linear regression. Based on the analysis of the data obtained the following results. 1. There are parental influence on learning outcomes IPS Integrated 2. There is the influence of study habits on learning outcomes IPS Integrated 3. There is the influence of the learning environment on learning outcomes IPS Integrated 4. There is the influence of parental guidance, study habits, and learning environments on learning outcomes IPS IntegratedKeywords: parental guidance, habit learning, learning environment, and integrated IPS learning outcomes